Awareness and Practice Patterns Among Pediatricians Regarding Retinopathy of Prematurity at Bharatpur, Chitwan, Nepal - Shrestha, Manisha; Giri Shrestha, Puspa; Sah, Ranjeet; Subedi, Kumudini (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Retinopathy of prematurity (ROP) is a disorder of the developing retina of preterm infants due to defective vasculogenesis that can lead to incurable blindness. It can be prevented by timely detection and treatment. The study aimed to analyze the level of awareness, knowledge and practice of Pediatricians regarding ROP in Bharatpur. Methods This was a quantitative, cross-sectional study using self-administered questionnaires to assess the awareness level among pediatricians at the main hospitals of Bharatpur City. A scoring system was implemented in the data analysis, depending on the correct chosen answers on the questionnaire. The ethical approval was obtained from the Institutional Review Committee of NNJS (Reg. no. 15/ 2022). Results Forty-three pediatricians from 11 hospitals in Bharatpur Metropolitan City filled out the questionnaires. The mean age of the participants was 35.53 ± 9.09 years (25 to 68 years), majority being male (N=28; 65.12%). More than half of the participants, 23 (53.49%) had a knowledge score of 10-15. The knowledge score was 0-5 and >20 in 6 (13.95%) and 2(4.65%) participants respectively. Men were significantly more knowledgeable about ROP than women (p = 0.02). Conclusions This study has projected the level of understanding about ROP among pediatricians in Bharatpur. Workshops and courses on ROP screening criteria and referral are recommended specifically for pediatric residents and pediatricians in the early stages of their careers. There should be coordination and good referral network between Pediatricians and Ophthalmologists.